Treatment of Effluent from a Factory of Paints Using Solar Photo-Fenton Process - Alam Gustavo Trovó; Oswaldo Gomes; Antonio Eduardo da Hora Machado (International Journal of Photoenergy)
We evaluated the use of Fenton reactions induced by solar radiation in the treatment of effluent from a factory of paints for buildings, after prior removal of the suspended solids. The increase of H2O2 concentration from 100 to 2500 mg L−1 for a [Fe2+] = 105 mg L−1 contributed to the reduction of DOC, COD, and toxicity. Our best results were achieved using 1600 mg L−1 H2O2, with 90% of DOC and COD removal and a complete removal of the toxicity with respect to Artemia salina. Additionally, through increasing Fe2+ concentration from 15 to 45 mg L−1, the DOC removal rate increased 11 times, remaining almost constant in the range above 45 until 105 mg L−1. Under our best experimental conditions, 80% of DOC removal was achieved after an accumulated dose of 130 kJ m−2 of UVA radiation (82±17 min of solar irradiation under an average UVA irradiance of 34.1±7.3 W m−2), while 40% of DOC removal was reached after 150 min under only thermal Fenton reactions. The results suggest the effectiveness of implementation of solar photo-Fenton process in the decontamination and detoxification of effluents from factories of paints for buildings.